Game Edukasi “Nihongo Kurabu” Belajar Bahasa Menggunakan Unity 2d Berbasis Android - Eka Wisnu Ramadhona; Tio Prasetya; Ade Irma Purnamasari; Arif Rinaldi Dikananda; Odi Nurdiawan (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2021)
Japan is one of the largest economies in the world and a developed country in the fields of technology and communication as well as industry. Many of our people are already interested in the Land of the Rising Sun, one of which is studying a foreign language, namely Japanese. Japanese is a language that is very much in demand by the people of Indonesia, many Indonesian people really like Japanese Pop Culture (Japanese Culture) such as Harujuku, Cosplay, J-Pop Music, Manga & Anime. However, due to the lack of learning media, some people still find it difficult to learn the language. For this reason, researchers created a 2D Nihongo Kurabu mobile game where this game consists of learning Japanese to make it easier for users to learn basic things and everyday language in Japanese. The research in this development uses the Waterfall method, in making 2D object game designs using the Paint Tool Sai v2 Software and Adobe Photoshop CC 2020, to continue the development stage of making games using Unity Software using the C# language. The trial of this game was carried out on SMK children in Cirebon. In the development of this game will produce an educational game on the Android Platform. The game consists of recognizing Hiraga-Katakana letters, everyday language, arranging words to find out the meaning of the word and the pronunciation of the word. In making this game using data collection techniques by conducting library research observations and interviews. It is hoped that this game educational application can make it easier for many people to learn Japanese. As a result, this game is a good solution in overcoming the problems of learning Japanese at SMK 1 Kedawung, where students can be motivated to learn Japanese anywhere and anytime.